INDONESIA’S STRATEGY AND POLICY TO FACE GLOBAL ECONOMIC UNCERTAINTY DURING AND AFTER COVID-19 - Harahap, Insan Harapan (Universitas Padjadjaran, 2026)
This article discusses Indonesia’s response to global economic uncertainty characterized by interrelated shocks such as pandemics, supply chain disruptions, geopolitical tensions, inflationary pressures, climate risks, and volatile commodity markets. The study applies a descriptive qualitative approach and uses secondary data derived from official government documents, macroeconomic statistics, international economic agency reports, scientific articles, and relevant literature. The analysis covers the period 2020-2025 to capture the emergency response and recovery phase amid ongoing global instability. These findings show that Indonesia is adopting an adaptive and multidimensional policy mix, incorporating expansionary fiscal measures, flexible monetary management, and long-term structural reforms to maintain macroeconomic stability and social welfare. Fiscal policy acts as a key stabilizer through targeted social assistance, subsidies, and incentives that support household consumption and business continuity. Monetary policy focuses on controlling inflation, maintaining exchange rate stability, and strengthening the financial system. Beyond stabilization, the government encourages economic diversification through industrial downstreaming, digital economy expansion, and strategic investments to reduce dependence on raw commodity exports. Food and energy security policies, and the acceleration of the energy transition, are the central pillars of long-term security. International cooperation further strengthens domestic efforts by expanding trade and investment partnerships. Despite relatively positive performance, structural challenges remain, especially commodity dependence, coordination gaps, and uneven human resource development. Overall, Indonesia’s experience underscores the importance of an integrated policy framework that aligns crisis management with inclusive and sustainable economic transformation under global uncertainty.